Evaluating the Importance of Monetary Policy Uncertainty: The Long- and Short-Term Effects and Responses. (April 2023) - Hu, Yang; Hong, Yanran; Feng, Kai; Wang, Jikai
Monetary policy changes have an irreplaceable impact on economic activity. Considering the close linkage among economic policies, we employ a bi-directional Granger causality test to investigate the potential linkages between monetary policy uncertainty (MPU) and other categorical economic policy uncertainty (CEPU) in the time and frequency domains. We consider all news-based U.S. categorical economic policy uncertainty indices (CEPU). All monthly CEPU indicators, covering January 1986 to January 2022, can be obtained from the website of Economic Policy Uncertainty. On an average, causality running from each CEPU to MPU is not apparent, while MPU can significantly affect six policy-related uncertainties: taxes, government spending, health care, national security, entitlement programs and regulation. A further frequency-domain study showed the dynamic changes in the relationship between them. For instance, we capture mid- and long-run causality running from tax uncertainty to MPU, while MPU has an impact on taxes in the medium run. Our findings provide policymakers with a better understanding of the nexus between MPU and other CEPU for formulating appropriate economic policies. Particularly, if a sectional government considers the long- and short-term effects of different policies when formulating strategies, risk transmission may be curbed to some extent.